2020
DOI: 10.1111/head.13925
|View full text |Cite
|
Sign up to set email alerts
|

Wear‐Off of OnabotulinumtoxinA Effect Over the Treatment Interval in Chronic Migraine: A Retrospective Chart Review With Analysis of Headache Diaries

Abstract: Objective To quantify wear‐off of the response to OnabotulinumtoxinA (OnabotA) treatment over the treatment cycle in chronic migraine at group and individual level. Background OnabotA administered quarterly is an effective treatment for chronic migraine. However, some patients report that headache recurs before the scheduled follow‐up injection. Methods In this retrospective chart review performed in 6 university outpatient centers or private practices specialized in headache treatment, 112 patients with a ≥30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
11
3
1
Order By: Relevance
“…RCTs and real-world studies proved that anti-CGRP mAbs have a modest wearing-off effect - symptom worsening just before the following treatment administration due to drug low levels at the end of its half-life 55 - which is lower than onabotulinumtoxinA. 65 , 66 Clinical experience suggests that efficacy of anti-CGRP mAbs persists throughout the entire treatment period and, in some cases, even after treatment discontinuation. 59 Data from real-world showed a delayed response to these treatments recommending a treatment duration of 3–6 months before declaring treatment failure due to non-response.…”
Section: Patient Profilesmentioning
confidence: 99%
“…RCTs and real-world studies proved that anti-CGRP mAbs have a modest wearing-off effect - symptom worsening just before the following treatment administration due to drug low levels at the end of its half-life 55 - which is lower than onabotulinumtoxinA. 65 , 66 Clinical experience suggests that efficacy of anti-CGRP mAbs persists throughout the entire treatment period and, in some cases, even after treatment discontinuation. 59 Data from real-world showed a delayed response to these treatments recommending a treatment duration of 3–6 months before declaring treatment failure due to non-response.…”
Section: Patient Profilesmentioning
confidence: 99%
“…Recently, in a retrospective study of 112 patients who had at least 30% BoNTA response, full BoNTA effect occurred in weeks 5 to 8. An increase in headache days was reported at the 12th and 13th weeks compared to the 5th and 8th weeks 14 . Our study was designed prospectively and follow-ups were done monthly, which allowed us to observe the monthly change in headache and analgesic intake.…”
Section: Discussionmentioning
confidence: 82%
“…However, the lack of difference in rates of “wearing off” between the galcanezumab 120 and 240 mg groups suggests that, on average, patients on higher doses do not have lower rates of “wearing off”. Another potential approach to counter “wearing off” is to use additional acute treatments toward the end of the dosing interval 12,13 . Further, encouraging patients to take their next dose of CGRP mAb within 30 days of the previous dose may also help diminish the likelihood of “wearing off”.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a post hoc analysis of a fremanezumab clinical trial showed no evidence of “wearing off” at the population‐level for patients with EM or CM on monthly or quarterly dosing regimens 10 . “Wearing off” has also been described with onabotulinumtoxinA in 23.3% to 62.9% of patients, most commonly 2 to 4 weeks before the next injection 11–14 …”
Section: Introductionmentioning
confidence: 99%